Chain based routing approach to improve lifespan in wireless body area networks - Lamia Sidhoum; Mourad Hadjila; Rachid Merzougui (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
One of the most significant limitations in wireless body area network (WBAN) is the requirement for low energy usage. For this reason, several routing techniques and protocols have been put out to provide an efficient means of energy saving during communication. In this work, we propose three approaches based on the formation of a chain of sensor nodes using a matrix of distances. The first approach is based on forming a single chain using the shortest distances. The second and the third consist in changing the position of the sink by forming a single cluster using the fuzzy C-means (FCM) method and the center of the latter constitutes the new position of the sink. In comparison to RE-ATTEMPT and PSOBAN, the third proposed chain-based approach has enabled a remarkable energy savings, which may have a big impact on the network’s entire lifespan.